(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
The development of digital technology has driven transformation in accounting information systems (AIS), improving efficiency and accuracy in financial data management. However, this progress is also accompanied by new challenges, especially related to information security risks such as cyber attacks, data leaks, and misuse of information. This research aims to analyze the concept of security in AIS and its implementation in the business world. Using the literature study method, this research examines various strategies implemented by companies to protect financial data, including the implementation of security policies, employee training, and the use of encryption technology and two-factor authentication (2FA). Case studies on PT Astra International and PT Herald Sulsel show that these measures are effective in improving the protection of financial information. However, challenges such as the increasing complexity of cyberattacks and lack of employee awareness are still obstacles that must be overcome. Therefore, strengthening security policies and continuous education for all stakeholders are needed so that accounting information systems remain safe and reliable in the face of evolving digital threats.